"Behind blue eyes": The valuation of knowing someone who attempted or died by suicide in Sweden - Daniela Andrén (Örebro University School of Business, 2025)
Advancing the economic understanding of suicide's externalities, this study uses the well-being valuation method (WVM) to quantify the exposure to suicide, specifically through knowing someone near, family, or friend (NFF) who attempted or died by suicide. First, using data from a survey of Swedish adults, we separately estimate several life satisfaction equations. For each equation, we use the same comparison group of individuals who reported never having been exposed to others' suicide, and compare them against different groups, each exposed to NFF-related suicide attempts or deaths. We find that income has a statistically significant positive impact on life satisfaction across all equations, and except for the experience of death alone, all other exposures to suicide have a statistically significant negative impact on life satisfaction. Next, we use these estimates to calculate the monetary compensation required to offset the decline in life satisfaction for individuals exposed to a NFF's suicide attempt or death. The required annual monetary compensation to offset this decline ranges from 6,400 to 9,910 euros, which suggests an economic value for mitigating the negative effects of suicide exposure equivalent to around a median monthly household income. However, our findings should be considered with caution when used to inform healthcare policies and prevention strategies aimed at reducing the spillover effects of exposure to suicide.
Keywords: 21; I12; I18; I31; 330; suicide exposure; suicide attempt; life satisfaction; suicide spillover; wellbeing valuation method; life satisfaction approach; Sweden